The innovation handbook : a nurse leader's guide to transforming nursing - Clipper, Bonnie; Sigma Theta Tau International (Indianapolis, IN : Sigma Theta Tau International, 2023)
'The ideal readers for this book are nurse leaders at all levels- including charge nurse managers, directors, and nurse executives-who are hoping to find inspiration, nuggets of insight, inspiration, or new ways of thinking about old problems. It doesn't matter if you have years of experience or are new to your role. Learning why we need to change, thinking about ways to change, and becoming a champion of change are all important, for all of us. Leading successful change is a numbers game. We need more trained leaders and direct care nurses with an innovative skill set to accomplish our goals. We are all students of change!'--
The current state of nursing and the need to transform -- Speaking the same language -- Culture as the foundation of innovation -- Leadership in turbulent times -- Creating a future-facing care model -- Leadership tools for transformation -- Leveraging technology on our terms.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
WorldCat record variable field(s) change: 650
Keywords: Nursing services -- Administration; Leadership; Organizational change; Nursing -- organization & administration; Leadership; Organizational Innovation; Change Management